Hauntology of Responsibility: Tom Stoppard’s Darkside - Tymon Adamczewski (Avant, 2017)
The article centres on the notion of responsibility in Tom Stoppard’s Darkside (2013). While Pink Floyd’s original album, which inspired the playwright, thematises its connection to ethics in a spectral and hauntological manner, through the use of field recording sound snippets interwoven in the music, the radio play explores the notion of responsibility through what is called “thought experiments.” The article identifies the subversive function of these narrative examples and, following Emanuel Levinas’ suggestions concerning the instability of the link between the philosophical discourse and that of examples, shows the latter’s insolent and disruptive nature. The notion of responsibility is further linked to its discussion by Jacques Derrida in his Gift of Death (1995) which consequently makes it possible to view the relation between responsibility and responding from a subversive, hauntological and undecidable perspective.